Square of the Lovers in Teruel - Linazasoro, José Ignacio (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2015)
The Square of the Lovers wasn’t strictly speaking a square, but the void in the fabric as a result of the bombings during the Civil War which struck the city. Nevertheless, there was an attempt during the Postwar, with more or less fortune, to transform that void into a square. They had the advantage of its central location and the dominant presence of the emblematic Tower of Saint Peter which, before the War, the same as the rest of the Mudejar towers in Teruel, had been built between houses and on the street, as a tower-door of the wall. But this situation had changed dramatically after the bombings, since the tower had been left isolated on one of its sides, allowing its vision from the lower part of the void which wanted to become the new square.